A survey on residents' satisfaction and developer performance: case of kasran bumi permai - Devani, Andita Putri; Muslichah, Istyakara (Jurnal Mantik, 2025)
This study aims to determine the satisfaction level of Kasran Bumi Permai residents with developer performance in four different aspects: personal and household, housing, neighborhood, and developer services. The study employs a quantitative approach, with data collected through questionnaires from 49 residents of Kasran Bumi Permai who participated in the survey. The data were then analyzed using descriptive analysis and Excel tools to test the validity and reliability of the research instrument; the tests were conducted to ensure that the research instrument - the questionnaire, had consistency and accuracy in measuring the respondents' satisfaction levels.  The findings show that residents of Kasran Bumi Permai are generally satisfied with the developer's performance. This includes satisfaction with the dwelling, neighborhood, developer services, greenery, cleanliness, tranquility, and security. This study also found that the level of residential satisfaction is influenced by a combination of personal characteristics, housing characteristics, neighborhood characteristics, and the quality of services provided by the developer. This study's findings can benefit Kasran Bumi Permai as a developer in its effort to improve resident satisfaction through improvements in aspects that still require attention, such as neighborhood, security, and greenery